2013
DOI: 10.1111/ijac.12024
|View full text |Cite
|
Sign up to set email alerts
|

Novel Layered Hydroxyapatite/Tri‐Calcium Phosphate–Zirconia Scaffold Composite with High Bending Strength for Load‐Bearing Bone Implant Application

Abstract: The integration of biological and mechanical requirements remains a challenge in developing porous hydroxyapatite (HA) and tri-calcium phosphate (TCP) scaffolds for load-bearing bone implant application. With the newly developed slipdeposition and coating-substrate co-sintering technique, a strong layered HA/TCP-zirconia scaffold composite structure was successfully fabricated. The bending strength (321 MPa) of this composite can match upper strength limit of the natural compact bone. The HA-based scaffold coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The implant pore size considered in this work is 100 μm because of its need to physically fit within the optimization layers and furthermore, such a porous structure can be manufactured using the method developed by our team . This involves a low‐density‐slip coating‐deposition and coating‐substrate cosintering process to deposit micro‐porous HA/tri‐calcium phosphate based coatings on zirconia substrate presintered at 900°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implant pore size considered in this work is 100 μm because of its need to physically fit within the optimization layers and furthermore, such a porous structure can be manufactured using the method developed by our team . This involves a low‐density‐slip coating‐deposition and coating‐substrate cosintering process to deposit micro‐porous HA/tri‐calcium phosphate based coatings on zirconia substrate presintered at 900°C.…”
Section: Discussionmentioning
confidence: 99%
“…A HA‐rich scaffold‐like coating on a strong HA‐containing substrate can be introduced during ceramic composite processing. Our group has recently developed a HA‐coating deposition method and the trials have yielded promising results using HA and zirconia to develop a system with graded porosity and material composition …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite is the most documented calcium phosphate and can be used in bulk form, as a coating and/or cements [2729]. This material can be classified according to its porosity, phase, and processing method.…”
Section: Hydroxyapatitementioning
confidence: 99%
“…Malmstrom et al in his study has demonstrated that bone in-growth in microporous HA scafold is more as compared to that of zirconia scafolds with same porosities [23]. On the other hand, it has been found that zirconia being instinctively tough adds to the strength of HA and TCP ceramics [24]. Matsumoto et al in his study conirmed excellent results in respect of strength comparable to human cortical bone using composite HA/zirconia scafold having 70/30 weight ratio [1].…”
mentioning
confidence: 92%